Comprehensive feature evaluation of the main facades of Catholic churches in Sichuan-Chongqing region based on semantic difference method, 1840–1949 - Qin Lai; Xinkai Li; Beibei Zhang; Nan Chen; YunZhang Li (PLoS ONE, 2026)
The existing Catholic churches constructed in the Sichuan-Chongqing region between 1840 and 1949, as precious carriers of Sino-Western cultural integration, have been listed in the cultural heritage protection catalog. This study employs the semantic difference method to conduct a quantitative evaluation of the main facade characteristics of these churches across five dimensions, operationalized through six specific evaluation criteria: relationship with the environment, facade contour, facade style 1 (Chinese vs. Western), facade style 2 (Folk vs. Official), facade decoration, and religious expression. The correlation between these facade features was also analyzed. The findings reveal: (1) Among the 62 existing Catholic churches in Sichuan and Chongqing, 14 are Chinese-style churches, accounting for 22.6%. (2) Facades demonstrate distinct cultural fusion: Chinese-style churches incorporate Western vertical composition elements, while Western-dominated churches integrate environmental harmony, Chinese architectural style, folk styles, and minimalist decoration. (3) According to the correlation analysis of Spearman’s correlation coefficient, the correlation coefficient between the facade style and decorative characteristics of the church is 0.857, and the correlation coefficient with religious expression is 0.754, showing a significant positive correlation. This study aims to provide a reference for the quantitative evaluation of cultural heritage facade characteristics and preservation of Sino-Western architectural cultural integration.